Constructing Core-Shell Co@N-Rich Carbon Additives Toward Enhanced Hydrogen Storage Performance of Magnesium Hydride - Wang, Ke; Deng, Qibo (Frontiers in Chemistry, 2020)
Magnesium hydride (MgH2) is regarded as a promising solid-state hydrogen storage materials, on account of its moderate-price and high gravimetric capacity. However, MgH2’s inferior kinetic of hydrogen release impedes its widespread application. In this work, we use core-shell Co@N-rich carbon (CoNC) additive as catalysts to ameliorate the performances of MgH2. The surface morphologic structures and hydrogen desorption kinetics of different MgH2-CoNC composites are systematically studied. We find that MgH2-5 wt% CoNC with the carbon contents of 17% (CoNC0) composites exhibit better hydrogen desorption performance. At 325 ℃, the MgH2-5 wt% CoNC0 composites can release up to 6.58 wt% of H2 in the 5 minutes, which is much higher than 0.3 wt% for pure MgH2. Our results demonstrate that importing the core-shell structured catalysts can effectively enhance the hydrogen release kinetics.